2021
DOI: 10.1002/wer.1623
|View full text |Cite
|
Sign up to set email alerts
|

A review of graphene‐TiO2 and graphene‐ZnO nanocomposite photocatalysts for wastewater treatment

Abstract: Technologies for wastewater remediation have been growing ever since the environmental and health concern is realized. Development of nanomaterials has enabled mankind to have different methods to treat the various kinds of inorganic and organic pollutants present in wastewater from many resources.Among the many materials, semiconductor materials have found many environmental applications due to their outstanding photocatalytic activities. TiO 2 and ZnO are more effectively used as photocatalyst or adsorbents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 320 publications
1
7
0
Order By: Relevance
“…Obviously, the hydroxyl ions and Fe 2+/ Fe 3+ species might have influenced the acid/base equilibrium of the wastewater [27]. This affirms other reported studies suggesting that the oxidative occurrence and reaction mechanism with organic substrates can occur in three phases [26,27]. This includes (a) hydrogen abstraction from aliphatic carbon atoms (1), (b) electrophilic addition to double bonds or aromatic rings ( 2) and (c) electron transfer reactions with a constant rate close to the circulation-controlled limit (3).…”
Section: The Preliminary Degradation Efficiencysupporting
confidence: 89%
See 1 more Smart Citation
“…Obviously, the hydroxyl ions and Fe 2+/ Fe 3+ species might have influenced the acid/base equilibrium of the wastewater [27]. This affirms other reported studies suggesting that the oxidative occurrence and reaction mechanism with organic substrates can occur in three phases [26,27]. This includes (a) hydrogen abstraction from aliphatic carbon atoms (1), (b) electrophilic addition to double bonds or aromatic rings ( 2) and (c) electron transfer reactions with a constant rate close to the circulation-controlled limit (3).…”
Section: The Preliminary Degradation Efficiencysupporting
confidence: 89%
“…Furthermore, when monitoring the recovered Fe-TiO 2 by the Ms, it was observed that at the onset of the process, there were no black precipitates on the Ms walls. However, at the end, there were black precipitates on the Ms walls, which suggests the iron (Fe 2+/ Fe 3+ ) of Fe-TiO 2 might have precipitated other contaminants [26][27][28]. Likewise, the decomposition of TiO 2 (Fe-TiO 2 ) might have resulted in the formation of OH• radicals, which increased photocatalytic activity [28].…”
Section: The Preliminary Degradation Efficiencymentioning
confidence: 99%
“…In order to further improve the photocatalytic performance of materials, people have explored numerous composites composed of TiO 2 and carbonaceous materials, such as carbon nanotubes (CNTs), activated carbons (ACs), and graphene (Gr). Compared with pure TiO 2 photocatalysts, Gr or graphite-like carbon has unique electronic properties, good transparency, flexibility, large theoretical specific surface areas, etc. …”
Section: Introductionmentioning
confidence: 99%
“…But it can be overcome by introducing other materials to associate with TiO 2 and help prevent the electron-hole pair recombination (Kale et al, 2020;Potle et al, 2020). Carbon-based materials, especially graphene-based nanomaterials, are suitable materials that can form nanocomposites with other materials (Barai et al, 2020;Thakre et al, 2021). When graphene-based material is introduced to TiO 2 , it synergistically enhances the photocatalytic performance of TiO 2 by preventing electronhole pair recombination by imparting high electron mobility (Bhanvase et al, 2017).…”
Section: Introductionmentioning
confidence: 99%